ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA PADA KEGIATAN BUDAYA KASEPUHAN CISITU LEBAK BANTEN - Suprianto, Suprianto; Riany, Meutia (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The study aims to examine the accountability and transparency of Village Fund management in supporting the Seren Taun cultural activity in Desa Kujangsari, Kecamatan Cibeber, Kabupaten Lebak. The research is based on concerns about limited cultural budgeting and weak public access to financial information.Methods: This research employs a qualitative descriptive approach, using interviews, observations, and financial document analysis to evaluate the stages of planning, implementation, administration, reporting, and accountability.Results: The findings show that most procedures align with regulatory requirements, although the planning stage does not meet the mandated timeline. Transparency is limited because the village publishes budget realization only through social media, without physical information boards. The allocation for Seren Taun is only 0.48 percent of the total village expenditure and is distributed as a cultural grant, with no detailed reporting from the traditional institution.Conclusion: Administrative compliance exists, but transparency and cultural fund reporting remain weak. The study recommends establishing reporting standards for cultural grants and increasing budget allocation for cultural preservation. Keywords: Accountability, Cultural Governance, Seren Taun, Transparency, Village Fund Management